Symbiotic Resonance, Nexus of Generative Influence, Ecologies of Innovation and Opportunity Exploitation among Small and Medium Enterprises - Mayanja, Samuel; Ntayi, Joseph M.; Omeke, Michael; Kibirango, Moses M.; Mutebi, Henry (Journal of African Business, 2022)
This paper used a quantitative cross-sectional survey design to collect data from 228 small and medium enterprises (SMEs) in Uganda to test the mediating role ecologies of innovation in the relationship between symbiotic resonance, nexus of generative influence and opportunity exploitation, but also, the moderating role of firm size in the relationship between symbiotic resonance and ecologies of innovation. The mediated – moderated hypotheses were tested through Partial Least Square Structural Equation Modeling (PLS-SEM) using SmartPLS version 3.3.0. The study found that ecologies of innovation positively and significantly mediate the relationship between nexus of generative influence and opportunity exploitation. Additionally, we confirmed that firm size moderates the relationship between symbiotic resonance and ecologies of innovation. Managers of SMEs and policy makers should pay more attention to situations where the owner/manager can act as a leader to influence employees positively, create an enabling environment, provide feedback, allow employee to deviate from norms.
Keywords: Symbiotic resonance; Nexus of generative influence; Ecologies of innovation; Opportunity exploitation; Firm size; SMEs